2014
DOI: 10.1364/ol.39.006110
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated polymer-based broadband terahertz wave modulator

Abstract: An optical broadband terahertz (THz) wave modulator, based on a polymer-inorganic interface, is investigated. The THz pulse transmission was efficiently modulated by an external continuous wave (CW) laser. The effects on the poly[2-methoxy-5-(2'-ethylhexyloxy)-1, 4-phenylenevinylene] (MEH-PPV)/silicon interface were measured by THz time-domain spectroscopy. The modulation factor reached 99.6%, at an external laser beam intensity of 6.3  W/cm2. In the proposed THz-CW system, a significant fall (in both THz tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Normally, photons carrying energy higher than the material bandgap are employed, which can be emitted by pulsed or continuous wave (cw) sources. The material of choice is typically silicon [40][41][42][43] or GaAs, which suggests the implementation of optical or nearinfrared lasers, typically 800 nm centered broadband fs-pulsed lasers. In all these experimental situations, the main limits in modulation depth and speed are arising from the substrate material rather than the illumination sources.…”
Section: All-optical Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, photons carrying energy higher than the material bandgap are employed, which can be emitted by pulsed or continuous wave (cw) sources. The material of choice is typically silicon [40][41][42][43] or GaAs, which suggests the implementation of optical or nearinfrared lasers, typically 800 nm centered broadband fs-pulsed lasers. In all these experimental situations, the main limits in modulation depth and speed are arising from the substrate material rather than the illumination sources.…”
Section: All-optical Devicesmentioning
confidence: 99%
“…[46] for 120 mW pump power by using a 405 nm cw laser. The modulation depth under optical pumping for both cw and pulsed THz radiation was reported to improve after spinning a polymer on the silicon substrate [43]. The effect was attributed to the increased electron-hole, electron-phonon, and electronimpurities scattering at the organic/inorganic boundary.…”
Section: All-optical Devicesmentioning
confidence: 99%
“…Our recent investigation of a THz-wave modulator based on a polymer-inorganic interface has shown that both transmission and reflection is attenuated under laser excitation, providing evidence supporting an absorption mechanism. 22 In this paper, we report on three THz wave amplitude modulators each incorporating a phthalocyanine compound (AlClPc, CuPc, or SnCl 2 Pc). The three organic/silicon bilayers were fabricated using thermal evaporation.…”
mentioning
confidence: 99%
“…22. A typical THz-TDS with a reliable bandwidth of 0.2-2.6 THz was used to obtain the THz optical parameters of the phthalocyanine films.…”
mentioning
confidence: 99%
See 1 more Smart Citation